Dedicated esophageal imaging may be unnecessary in marijuana-associated spontaneous pneumomediastinum: Findings from a retrospective cohort study - Yu, Irene; Tung, Kaity; Dugan, Ryanne; Qaqish, Robert Thamer; Perry, Yaron (Frontiers in Surgery, 2023)
Background: Marijuana use has become more common since its legalization, as have reports of marijuana-associated spontaneous pneumomediastinum. Non-spontaneous causes such as esophageal perforation are often ruled out on presentation due to the severe consequences of untreated disease. Here we seek to characterize the presentation of marijuana-associated spontaneous pneumomediastinum and explore whether esophageal imaging is necessary in the setting of an often benign course and rising healthcare costs. Materials and Methods: Retrospective review was performed for all 18-55 year old patients evaluated at a tertiary care hospital between 1/1/2008 and 12/31/2018 for pneumomediastinum. Iatrogenic and traumatic causes were excluded. Patients were divided into marijuana and control groups. Results: 30 patients met criteria, with 13 patients in the marijuana group. The most common presenting symptoms were chest pain/discomfort and shortness of breath. Other symptoms included neck/throat pain, wheezing, and back pain. Emesis was more common in the control group but cough was equally prevalent. Leukocytosis was present in most patients. Four out of eight of computed tomography esophagarams in the control group showed a leak requiring intervention, while only one out of five in the marijuana group showed even a possible subtle extravasation of contrast but this patient was ultimately was managed conservatively given the clinical picture. All standard esophagrams were negative. All marijuana patients were managed without intervention. Discussion: Marijuana-associated spontaneous pneumomediastinum appears to have a more benign clinical course compared to non-spontaneous pneumomediastinum. Esophageal imaging did not change management for any marijuana cases. Perhaps such imaging could be deferred if clinical presentation of pneumomediastinum in the setting of marijuana use is not suggestive of esophageal perforation. Further research into this area is certainly worth pursuing.